Vigor tests to evaluate the physiological quality of Sebastiania commersoniana (Baill.) Smith & Downs seeds - Garcia dos Santos, Sergio Roberto; Paula, Rinaldo Cesar de [UNESP] (Ipef-inst Pesquisas Estudos Florestais, 2009)
The objective of this work was to evaluate the efficiency of different vigor tests to assess S. commersoniana seeds physiological quality during storage. Therefore, seeds were stored in cloth bags, plastic bags and glass containers for 531 days, both at room temperature and in a cold chamber. Periodically samples were taken and the following tests were conducted: standard germination, germination speed index, first count after germination, seedlings fresh and dry matter, electrical conductivity (imbibitions for 2 and 24 hours) and accelerated aging, in order to monitoring the seeds physiologic quality. Data were submitted to polynomial regression analysis, for each of the combination of packaging/storage condition. The results obtained led to the following considerations: a) the speed germination index and the accelerated aging test permitted a good evaluation of the seed-lots quality; b) the first count of germination did not allow any prediction about seed lots vigor; c) seedling fresh and dry matter did not discriminate among seed lots; d) electrical conductivity test after 2 h imbibitions was not adequate to evaluate the seed lots vigor and e) the electric conductivity test with 24 h imbibitions was more adequate to differentiate among seed lots, but with little efficiency to discriminate among seed lots with intermediate vigor or with low quality differences.
Keywords: Seed storage; Accelerated aging; Electrical conductivity; Seedlings performance